2016
DOI: 10.1007/s00439-016-1749-4
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variability in Parkinson’s disease: assembling the puzzle through a systems biology approach

Abstract: Parkinson’s disease (PD), the second most common progressive neurodegenerative disorder of aging, was long believed to be a non-genetic sporadic origin syndrome. The proof that several genetic loci are responsible for rare Mendelian forms has represented a revolutionary breakthrough, enabling to reveal molecular mechanisms underlying this debilitating still incurable condition. While single nucleotide polymorphisms (SNPs) and small indels constitute the most commonly investigated DNA variations accounting for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 161 publications
(211 reference statements)
0
39
0
Order By: Relevance
“…Despite the amount of research on this neurodegenerative disease, its origin remains unclear. Only 5-10% of cases have a genetic background [2][3][4][5], while the rest are of idiopathic origin [6], although some risk factors have been identified, such as age, environmental toxins, and infections [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the amount of research on this neurodegenerative disease, its origin remains unclear. Only 5-10% of cases have a genetic background [2][3][4][5], while the rest are of idiopathic origin [6], although some risk factors have been identified, such as age, environmental toxins, and infections [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, genomic studies of individuals with developmental or neurodegenerative diseases have tremendously advanced our understanding of the genetics of these disorders [ 1 5 ]. Many of them, including autism spectrum disorder (ASD), schizophrenia, Alzheimer’s disease (AD), and Parkinson’s disease (PD), are caused by a heterogeneous combination of variant alleles and have therefore proven difficult to recapitulate in animal models, which are better suited for studying single-gene mutations [ 6 9 ]. Although the human brain is the ideal model to study human neuropathology, the limited availability of healthy and diseased brain tissue as well as the difficulties with culturing or genetically manipulating the tissue makes this an inopportune model with which to easily elucidate molecular mechanisms underlying these disorders.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that multiplications of SNCA are observed in around 0.05% of European PD patient populations . Other genes related to hereditary forms of PD have copy number variations (CNVs) demonstrating the role of loss of function . CNVs in SNCA , however, seem to suggest a gain of function.…”
mentioning
confidence: 99%